Perspectives on the Factors Affecting Students’ Dropout Rate During COVID-19: A Case Study From Pakistan - Anita Shuja; Akhtar Ali; Sana Shuja Ahmad Khan; Shafiqa Bilal Burki; Shaham Bilal (SAGE Open, 2022)
Education has always been considered as the linchpin for a country’s economic and social development. The dropout rate in schools especially in developing countries has always been a problematic issue and the situation has further been worsened by the COVID-19 pandemic. This study primarily aims at studying the factors affecting the school dropout rate during the pandemic. Lockdown is the first step that any country starts to adopt for the safety of its general public. This severely affects the masses’ financial conditions, especially for the parents of students at risk, as the dropout rate increases with financial pressures. The slogan “stay home stay safe” has further aggravated the fear of the parents to send their children out and attend schools. The data for the study was collected from 20 public and private schools of two divisions, including seven districts of the province of Punjab, Pakistan, using interviews of policymakers, parents of dropouts, teachers, and students. The study is a corollary to several issues already highlighted in various other articles to transpire the details of drop-out rates in developing countries in general and Pakistan in particular. The study revealed financial conditions, lockdown effects, mode of learning, government policies, fear of death, the psyche of the parents, socio-cultural effects, the role of teachers and administrators, most affected level, and some contributory factors amongst the major factors. Finally, the study analyzes the effects of dropout and will help suggest measures to control the dropout rate in Pakistan in particular and developing countries in general.